G/s parabol đã cho luôn đi qua 1 điểm cố định có tọa độ (xo ; yo)
Điều đó nghĩa là : \(y_o=mx_o^2+\left(m-1\right)x_o-6m\) đúng \(\forall m\)
\(\Leftrightarrow m\left(x_o^2-x_o-6\right)-x_o-y_o=0\) đúng \(\forall m\)
\(\Leftrightarrow\left\{{}\begin{matrix}x_o^2-x_o-6=0\\-x_o-y_o=0\end{matrix}\right.\) \(\Leftrightarrow\left\{{}\begin{matrix}\left[{}\begin{matrix}x_o=3\\x_o=-2\end{matrix}\right.\\x_o+y_o=0\end{matrix}\right.\) \(\Leftrightarrow\left[{}\begin{matrix}x_o=3;y_o=-3\\x_o=-2;y_o=2\end{matrix}\right.\)
Parabol luôn đi qua 2 điểm cố định có tọa độ (3;-3) và (-2;2)